Development of the Robert Wood Johnson Foundation National Survey of Health Attitudes Description and Top-Line Summary Data - Carman, Katherine Grace (RAND Corporation, 2016)
This report describes the Robert Wood Johnson Foundation's National Survey of Health Attitudes, part of the foundation's Culture of Health strategy. The foundation undertook this survey to measure key constructs that could not be measured in other data sources, primarily addressing the action area making health a shared value. The report describes the survey development and provides the text of the survey and summary statistics of the data.